Comparative Study of Using Folly Catheter Balloon and Syntocinon for Cervical Ripening - A. Malakzadeghan; M. Nazemi; M. Kashanian; H. Haghani (Iran University of Medical Sciences, 2008)
Background & Aim: Cervical ripening is one of the methods used for cervical preinduction with the aim of facilitating labor and ending pregnancy. There are various recommendations on using labor inducing methods, but no preferred method has been known. The aim of this study was to compare the results of using folly catheter balloon and oxytocin for cervical induction.  Material & Method: It was a randomized clinical trial. Two hundred and seventy pregnant women attending Shahid Akbarabadi center were recruited and randomly assigned to one of the 3 groups. The women in the first and second group were catheterized and their catheters were fixed using 30 cc and 80cc of normal saline respectively. The third group just received 5 units of syntocinon in 1000 ml IV solution.  Results: There were statistically significant difference between 3 groups in bishop score after cervical preparation (P=0.000). Moreover, there were statistically significant difference between folly catheter groups and syntocinon group regarding type of labour (P=0.000), the time intervals between induction and the active phase of labour (P=0.000), and induction and labour (P=0.000). The duration of the third stage and time interval between the third stage and labour were much shorter in catheter groups than syntocinon group.  Conclusion: Using folly catheter balloon for ending pregnancy is effective and has no risk. Moreover, it has lees complications and more desirable delivery outcomes than oxytocin. Cervical ripening is also effective in the mode of delivery and reduces the need for surgical interventions and also the costs of hospitalization.